Defined Conjugation of Glycans to the Lysines of CRM197 Guided by their Reactivity Mapping. Issue 6 (11th March 2014) - Crotti, Stefano; Zhai, Huili; Zhou, Jing; Allan, Martin; Proietti, Daniela; Pansegrau, Werner; Hu, Qi‐Ying; Berti, Francesco; Adamo, Roberto
Abstract Systematic characterisation of the reactivity of the lysine moieties in CRM197 towards N‐hydroxysuccinimide linkers bearing alkynes or azides is described. This involves two‐step conjugation of various glycans to CRM197 by click chemistry in a well‐defined manner. By semiquantitative LC‐MS/MS analysis of proteolytic digests of the conjugates formed, the reactivity of lysine residues in the protein was mapped and ranked. Computational analysis of the solvent accessibility of each lysine residue (based on the CRM197 crystal structure) established a correlation between reactivity and surface exposure. By this approach, conjugation involving lysine residues (normally a random process) can be controlled. It enables the preparation of lysine‐mediated glycoconjugates with improved batch‐to‐batch reproducibility, thereby producing neo‐glycoconjugates with more‐consistent biological activity.